Task sharing in an interprofessional medication management program: a survey of general practitioners and community pharmacists - Möcker, Robert; Weißenborn, Marina; Klingenberg, Anja; Wirbka, Lucas; Eickhoff, Christiane; Schulz, Martin; Kaufmann-Kolle, Petra; Donner, Susanne; Maywald, Ulf; Meid, Andreas; Ruff, Carmen; Stoll, Felicitas E.; et al. (BMC health services research, 2022)
Pharmacist-led medication review and medication management programs (MMP) are well-known strategies to improve medication safety and effectiveness. If performed interprofessionally, outcomes might even improve. However, little is known about task sharing in interprofessional MMP, in which general practitioners (GPs) and community pharmacists (CPs) collaboratively perform medication reviews and continuously follow-up on patients with designated medical and pharmaceutical tasks, respectively. In 2016, ARMIN (Arzneimittelinitiative Sachsen-Thüringen) an interprofessional MMP was launched in two German federal states, Saxony and Thuringia. The aim of this study was to understand how GPs and CPs share tasks in MMP when reviewing the patients’ medication.